(untitled) (mathematica didactica, 2009)
Mathematical abilities can develop especially optimal when they are based on the previous knowledge and skills of the children. This is also valid for the abilities in solving problems. Only the look at developments and distinctive features of development whilst handling mathematical texts and methodical-didactic conclusions drawn from them allow a purposeful organization of individual processes of learning in this area. The following study presented as an extract is devoted to the two fields of research being closely linked with each other, to the pre-conditions of the learners and the coordinated accompanying and instructing by the teachers.